Prospects for cereal self-sufficiency in sub-Saharan Africa - Ittersum, Martin K. van; Alimagham, Seyyedmajid; Silva, João Vasco; Adjei-Nsiah, Samuel; Baijukya, Frederick P.; Bala, Abdullahi; Chikowo, Regis; Grassini, Patricio; de Groot, Hugo L.E.; Nshizirungu, Aphrodis; Mahamane Soulé, Abdelkader; Sulser, Timothy B.; et al. (National Academy of Sciences, 2025)
Sub-Saharan Africa (SSA) has the world’s largest projected increase in demand for food. Increased dependence on imports makes SSA vulnerable to geopolitical and economic risks, while further expansion of agricultural land is environmentally harmful. Cereals, in particular, maize, millet, rice, sorghum, and wheat, take nearly 50% of the cropland and 43% of the calories and proteins consumed in the region. Demand is projected to double until 2050. Here, we assess recent developments in cereal self-sufficiency and provide outlooks until 2050 under different intensification, area expansion, and climate change scenarios. We use detailed data for ten countries. Cereal self-sufficiency increased between 2010 and 2020 from 84 to 92% despite the 29% population increase. The production increase was achieved by increased yields per hectare (44%), area expansion (34%), and a shift from millet to the higher yielding maize (22%). Outlooks for 2050 are less pessimistic than earlier assessments because of the larger 2020 baseline area, higher shares of maize and somewhat less steep projected population increase. Yet, to halt further area expansion, a drastic trend change in annual yield increase from the present 20 to 58 kg ha−1 y−1 is needed to achieve cereal self-sufficiency. While such yield increases have been achieved elsewhere and are feasible given the yield potentials in SSA, they require structural changes and substantial agronomic, socioeconomic, and political investments. We estimate that amounts of added nitrogen need to at least triple to achieve such yield improvements, but it is essential that this comes with improved context-specific agronomy.